Size and Development of the Shadow Economies of 157 Countries Worldwide: Updated and New Measures from 1999 to 2013 - Mai Hassan; Friedrich Schneider (Institute for the Study of Labor (IZA), 2016)
This paper is a first attempt to study the size and development of the shadow economies of 157 countries over 1999 to 2013. Using a MIMIC model, we find that higher tax and regulatory burden, unemployment and self-employment rates are drivers of the shadow economy, meaning that an increase of these causal variables increases the shadow economy. Our result also confirms previous findings of Friedrich Schneider, Andreas Buehn and Claudia Montenegro (2010). The estimated average of informality of 157 countries around the world, including developing, eastern European, central Asian and high income OECD countries averaged over 1999 to 2013 is 33.77% of official GDP. A critical discussion about the size of these macro-estimates comes to the conclusion that most likely the "true" shadow economy of these countries is only 69% of their estimated macro-MIMIC-values.
Keywords: C51; C82; E26; E41; H11; H26; 330; shadow economies of 157 countries; quality of institutions; tax and regulatory burden; MIMIC model